PEMELIHARAAN ALUR PELAYARAN DI SUNGAI BARITO - Sugeng, Sunarso (Department of Naval Architecture - Diponegoro University, 2009)
Study this paper is to analyse to dimension groove Barito River navigation , existing plan this time to get dimension groove appropriate sea transport of technical conditions for the shake of safety, security and fluency accomodated by ship dimension - ship getting through it especially for the merchantman of big ship and, most ideal dredging volume is 1,537,261.48m3 that way there is addition of deepness groove from 5m becoming 5,4m LWS and wide reduction of path sea transport of external sill River Barito from 100m becoming 96m, so that can be supporting productivity of Port Trisakti because ship loadedly 5m can enter path during 24 hours in day without depended ebb .